Inhibition of HIV-1 Gag–membrane interactions by specific RNAs - Todd, Gabrielle C. (RNA, 2017)
HIV-1 particle assembly, which occurs at the plasma membrane (PM) of cells, is driven by the viral polyprotein Gag. Gag recognizes phosphatidylinositol-(4,5)-bisphosphate [PI(4,5)P(2)], a PM-specific phospholipid, via the highly basic region (HBR) in its N-terminal matrix (MA) domain. The HBR is also known to bind to RNA. We have previously shown, using an in vitro liposome binding assay, that RNA inhibits Gag binding to membranes that lack PI(4,5)P(2). If this RNA block is removed by RNase treatment, Gag can bind nonspecifically to other negatively charged membranes. In an effort to identify the RNA species that confer this inhibition of Gag membrane binding, we have tested the impact of purified RNAs on Gag interactions with negatively charged liposomes lacking PI(4,5)P(2). We found that some tRNA species and RNAs containing stem–loop 1 of the psi region in the 5′ untranslated region of the HIV-1 genome impose inhibition of Gag binding to membranes lacking PI(4,5)P(2). In contrast, a specific subset of tRNAs, as well as an RNA sequence previously selected in vitro for MA binding, failed to suppress Gag–membrane interactions. Furthermore, switching the identity of charged residues in the HBR did not diminish the susceptibility of Gag–liposome binding for each of the RNAs tested, while deletion of most of the NC domain abrogates the inhibition of membrane binding mediated by the RNAs that are inhibitory to WT Gag–liposome binding. These results support a model in which NC facilitates binding of RNA to MA and thereby promotes RNA-based inhibition of Gag–membrane binding.